Data-driven law : data analytics and the new legal services - Walters, Edward J.; Taylor and Francis (Boca Raton, FL : Auerbach Publications, an imprint of Taylor and Francis, 2018)
For increasingly data-savvy clients, lawyers can no longer give "it depends" answers rooted in anecdata. Clients insist that their lawyers justify their reasoning, and with more than a limited set of war stories. The considered judgment of an experienced lawyer is unquestionably valuable. However, on balance, clients would rather have the considered judgment of an experienced lawyer informed by the most relevant information required to answer their questions. Data-Driven Law: Data Analytics and the New Legal Services helps legal professionals meet the challenges posed by a data-driven approach to delivering legal services. Its chapters are written by leading experts who cover such topics as: Mining legal dataComputational lawUncovering bias through the use of Big DataQuantifying the quality of legal servicesData mining and decision-makingContract analytics and contract standardsIn addition to providing clients with data-based insight, legal firms can track a matter with data from beginning to end, from the marketing spend through to the type of matter, hours spent, billed, and collected, including metrics on profitability and success. Firms can organize and collect documents after a matter and even automate them for reuse. Data on marketing related to a matter can be an amazing source of insight about which practice areas are most profitable.Data-driven decision-making requires firms to think differently about their workflow. Most firms warehouse their files, never to be seen again after the matter closes. Running a data-driven firm requires lawyers and their teams to treat information about the work as part of the service, and to collect, standardize, and analyze matter data from cradle to grave. More than anything, using data in a law practice requires a different mindset about the value of this information. This book helps legal professionals to develop this data-driven mindset.
chapter 1 Introduction: Data Analytics for Law Firms -- Using Data for Smarter Legal Services / Ed Walters -- chapter 2 Mining Legal Data: Collecting and Analyzing 21st Century Gold / A. Grady Kenneth -- chapter 3 Deconstructing Contracts: Contract Analytics and Contract Standards / Kingsley Martin -- chapter 4 The Big Move Toward Big Data in Employment / Aaron Crews -- chapter 5 Computational Law, Symbolic Discourse, and the AI Constitution / Stephen Wolfram -- chapter 6 Quantifying Success: Using Data Science to Measure the Accuracy of Technology-Assisted Review in Electronic Discovery / R. Grossman Maura V. Cormack Gordon -- chapter 7 Quantifying the Quality of Legal Services: Data Science Lessons from Avvo / Nika Kabiri Ed Sarausad Rahul Dodhia -- chapter 8 Uncovering Big Bias with Big Data: An Introduction to Linear Regression / David Colarusso -- chapter 9 Data Mining in the Law Firm: Using Internal Expertise to Drive Decision Making / Kumar Jayasuriya -- chapter 10 Can Intrapreneurship Solve the Innovator$1 (Bs Dilemma? Law Firm Examples /s Bill Henderson.
Keywords: COMPUTERS / Database Management / Data Mining; LAW / Criminal Law / General; Big data; Electronic data processing; Electronic discovery (Law); Information storage and retrieval systems -- Law